Surgical activity in England and Wales during the COVID-19 pandemic: a nationwide observational cohort study. (August 2021) - Dobbs, Thomas D.; Gibson, John A.G.; Fowler, Alex J.; Abbott, Tom E.; Shahid, Tasnin; Torabi, Fatemeh; Griffiths, Rowena; Lyons, Ronan A.; Pearse, Rupert M.; Whitaker, Iain S.
Abstract: Background: A significant proportion of healthcare resource has been diverted to the care of those with COVID-19. This study reports the volume of surgical activity and the number of cancelled surgical procedures during the COVID-19 pandemic. Methods: We used hospital episode statistics for all adult patients undergoing surgery between January 1, 2020 and December 31, 2020 in England and Wales. We identified surgical procedures using a previously published list of procedure codes. Procedures were stratified by urgency of surgery as defined by NHS England. We calculated the deficit of surgical activity by comparing the expected number of procedures from 2016 to 2019 with the actual number of procedures in 2020. Using a linear regression model, we calculated the expected cumulative number of cancelled procedures by December 31, 2021. Results: The total number of surgical procedures carried out in England and Wales in 2020 was 3 102 674 compared with the predicted number of 4 671 338 (95% confidence interval [CI]: 4 218 740–5 123 932). This represents a 33.6% reduction in the national volume of surgical activity. There were 763 730 emergency surgical procedures (13.4% reduction) compared with 2 338 944 elective surgical procedures (38.6% reduction). The cumulative number of cancelled or postponed procedures was 1 568 664 (95% CI: 1 116 066–2 021 258). We estimate that this will increase to 2 358 420 (95% CI: 1 667 587–3 100 808) up to December 31, 2021. Conclusions: The volume of surgical activity in England and Wales was reduced by 33.6% in 2020, resulting in more than 1.5 million cancelled operations. This deficit will continue to grow in 2021.